Building Consumer Loyalty in Digital Payment Ecosystems through E-Trust and Service Excellence - Mimbha Nur Indahsari; Nur Diana; Moh. Cholid Mawardi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of E-Service Quality and Brand Image on Customer Loyalty among QRIS ShopeePay users, with E-Trust as a mediating variable, among Generation Z in Malang City. The hypotheses proposed include direct and indirect effects among the variables in the research model. This study employs a quantitative approach using an explanatory-causal research design. Data were collected via an online questionnaire distributed to 119 respondents Generation Z users of ShopeePay QRIS in Malang City using a non-probability sampling technique. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method via SmartPLS 4.0 software. The results of the study indicate that E-Service Quality and Brand Image have a positive and significant effect on Customer Loyalty, and E-Service Quality also has a positive and significant effect on E-Trust. Meanwhile, Brand Image does not have a significant effect on E-Trust. E-Trust was found to have a positive and significant effect on Customer Loyalty and significantly mediates the effect of E-Service Quality on Loyalty; however, it does not mediate the effect of Brand Image on Loyalty. These findings indicate that service quality and trust are key factors in shaping user loyalty, particularly among Generation Z, who prioritize user experience over brand perception. The implications of this study suggest that digital service providers, particularly ShopeePay, need to focus their strategies on improving service quality, system security, and user experience to strengthen customer trust and loyalty. Further research is recommended to include additional variables, expand the scope of the study, and employ a more diverse methodological approach to obtain more comprehensive results.